Mechanism of inflammasomes in cancer and targeted therapies - Gu, Qingdan; Zou, Jiazhen; Zhou, Ying; Deng, Qiuchan (Frontiers in Oncology, 2023)
Inflammasomes, composed of NOD-like receptors (NLRs), are immune-functional protein multimers that are closely linked to the host defense mechanism. When NLRs sense pathogen-associated molecular patterns (PAMPs) and damage-associated molecular patterns (DAMPs), they assemble into inflammasomes. Inflammasomes can activate various inflammatory signaling pathways, including NF-κB and MAPK signaling pathways, and produce a large number of proinflammatory cytokines, which are closely associated with multiple cancers. They can also accelerate the occurrence and development of cancer by providing suitable tumor microenvironments, promoting tumor cell proliferation, and inhibiting tumor cell apoptosis. Therefore, the exploitation of novel targeted drugs against various inflammasomes and proinflammatory cytokines is a new idea for the treatment of cancer. In recent years, more than 50 natural extracts and synthetic small molecule targeted drugs have been reported to be in the research stage or have been applied to the clinic. Herein, we will overview the mechanisms of inflammasomes in common cancers and discuss the therapeutic prospects of natural extracts and synthetic targeted agents.